Evaluation of Immune Response to Hepatitis B Vaccine among Malnourished Children in Yemen - Fuad A. Alsamei; Atif A. Elagib; Najla A. Al-Sonboli; Fawzi A. Alkumaim; Nader S. Alsayaad; Abdulmalik T. Aldobibi (Yemeni Journal for Medical Sciences, 2015)
Objectives: To determine the coverage rate of hepatitis B virus (HBV) vaccine and to evaluate the immune response to HBV vaccine by measuring hepatitis B surface antibody (anti-HBs) among malnourished under-five-year old children.